2020
DOI: 10.1007/s10013-020-00443-x
|View full text |Cite
|
Sign up to set email alerts
|

Theta Surfaces

Abstract: A theta surface in affine 3-space is the zero set of a Riemann theta function in genus 3. This includes surfaces arising from special plane quartics that are singular or reducible. Lie and Poincaré showed that any analytic surface that is the Minkowski sum of two space curves in two different ways is a theta surface. The four space curves that generate such a double translation structure are parametrized by abelian integrals, so they are usually not algebraic. This paper offers a new view on this classical top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…He also gave a complete classification of the types of theta divisors that are algebraic in [9]. Some of Eiesland's examples are reconsidered in [2]. In this paper, we will continue this study of algebraic theta divisors and theta functions in all dimensions.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…He also gave a complete classification of the types of theta divisors that are algebraic in [9]. Some of Eiesland's examples are reconsidered in [2]. In this paper, we will continue this study of algebraic theta divisors and theta functions in all dimensions.…”
Section: Introductionmentioning
confidence: 90%
“…Finally, the theta divisor is also an example of a double translation hypersurface: this is a hypersurface with two distinct parametrizations as Minkowski sums of curves. Their study goes back to Sophus Lie, and modern treatments can be found in [16] and in [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be worthwhile to discover more about possible connections of the Hirota variety with the soliton solutions [13,Example 11], also its potential link to the Dubrovin variety. In dimension 3, the Riemann theta function degenerations recover the so-called theta surfaces [10], classically the double translation surfaces [157]. For highly singular curves, these surfaces happen to be algebraic.…”
Section: Algebraic Statistics By Aida Marajmentioning
confidence: 99%
“…. , c ig ) specifies a linear form c T i z = g j=1 c ij z j , just like in (2). The coefficients a = (a 1 , a 2 , .…”
Section: Introductionmentioning
confidence: 99%